Capturing the semantic relationship between clinical terms with current MeSH bibliographic coding - Miller, Perry L.; Smith, Paula; Morrow, Jon S.; Riely, Caroline A.; Powsner, Seth M. (Computer methods and programs in biomedicine, 1988)
This paper compares bibliographic retrieval using current MeSH (Medical Subject Headings) to bibliographic retrieval using explicitly coded semantic relationships between index terms. In a previous study, ten lists of abstracts, each list containing 20–40 papers discussing a specific pair of terms, were analyzed to identify the specific relationship(s) between those terms discussed in each paper. In the present study, we analyze how well current MeSH coding, using topical subheadings and check tags, can selectively retrieve those papers discussing each semantic relationship.